Derivatives in the wake of disintermediation: a simultaneous equations model of commercial and industrial lending and the use of derivatives by US banks. (1st January 2012) - Ashraf, Dawood; Goddard, John
Before the financial crisis of 2007–2009, the search for new revenue and profit streams by US banks contributed to a long-term trend towards disintermediation. Trading in derivatives might offer an alternative to traditional deposit-taking and lending business as a source of revenue and profit; or it might enable banks to increase their lending more rapidly, through improved risk management. A simultaneous equations model is developed for the growth in commercial and industrial lending, and the use of derivatives. Lending by derivatives users grew more slowly on average, and the likelihood of using derivatives was inversely related to the growth of lending. This suggests the use of derivatives was a substitute for traditional lending business. Dealing in derivatives creates new forms of systemic risk through complex and opaque patterns of exposure. The empirical results suggest a continuing need for careful regulatory oversight, and more transparent disclosure of banks' derivatives exposures.